Determination Of The ABO and Rh -Hr Systems At 350 Mestizos Boarding In Hospital Dos De Mayo - Quesada Velásquez, Norberto (1967)
The discovery of the ABO system agglutinogen corresponding , by Karl Landsteiner earlier (7) century marked the beginning of a new era in the field of hematology , classifying people into four blood groups, based on the fact that antigens A and B can be together, or individually absent. These groups started finding a large number , counting today with nine clearly defined systems and two systems like Diego and Sutter , which could be the tenth and eleventh, and even have been described several "private" antigens or low incidence and "public " or high incidence . Since the early work on blood groups in the determination of ABO and Rh -Hr system , carried out by several researchers as Landsteiner and Wiener in 1941 (5); Landsteiner , Wiener and Matson in 1942 (6); and Levin and Wong in 1943 (9) , have been made ​​in most of the peoples of the world, have the greatest practical importance , due to the frequent use of transfusions in our modern medicine and also to the presence of isosensibilizaciones , as in the case of fetal erythroblastosis.